Remediation of metal contaminated soils - Marsz, Aleksandra Monika (2014)
The efficiency of contaminant stabilization in soil treated with zero-valent iron (ZVI) should be evaluated in long-term experiments, as stabilization techniques do not decrease total metal concentration. With time, properties of soil can change and iron hydroxides can crystalize, what can lead to a release of contaminants. This study evaluates the influence of ZVI on arsenic, copper, cadmium and nickel solubility in contaminated soils after 16 and 6 years after applying the treatment. The soils were treated with 1% iron grit (Reppel and Louis Fargues) and 2% iron grit (Biogeco). Louis Fargues soil was additionally treated with sewage sludge and sewage sludge with addition of 1% iron grit. Batch equilibrium experiments were performed to investigate solubility of metals in a wide pH-range (3-9). Observed solubility was evaluated using the geochemical equilibrium program Visual MINTEQ (Cu and As). Batch experiments showed that ZVI addition did not have an influence on cadmium and nickel solubility, whereas the solubility of arsenic decreased significantly (approximately a factor of ten). Influence on copper was pH dependent – at ambient pH (ca. 6.5) the solubility was significantly reduced. In contrast, the solubility at lower pH remained the same in control and ZVI-treated soils. This behaviour could be mimicked with Visual MINTEQ, strengthening the validity of these data. This study suggest that ZVI addition can be a suitable remediation method for As and Cu, also in a long-term-perspective. For Cu pH needs to be kept at about 7, since binding strength of Cu by ferric (hydr)oxides decreases with decreasing pH.